2021
DOI: 10.1155/2021/5560386
|View full text |Cite
|
Sign up to set email alerts
|

1927 nm Thulium Laser Successfully Treats PostInflammatory Hyperpigmentation in Skin of Color

Abstract: Background. Treatment of postinflammatory hyperpigmentation (PIH) in patients with dark skin is challenging as the treatment itself might provoke paradoxical PIH. Only few studies examined the safety and efficacy of nonablative laser treatment in these patients. The objective was to examine efficacy and safety of nonablative 1927 nm wavelength laser followed by bleaching creams in the treatment of PIH. Methods. It was a prospective interventional pilot study that was conducted during 2019. All patients were of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…After title/abstract screening of 2157 articles and full text review of 166 articles, ultimately 41 articles were included in this study representing 877 patients (Figure 1, Table S1). 10–50 Ten studies were level of evidence 1, 30 studies were level of evidence 2, and 1 study was level of evidence four. Study types included placebo‐controlled trials ( n = 2), non‐placebo‐controlled trials ( n = 8), cohort studies ( n = 30) and case series ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…After title/abstract screening of 2157 articles and full text review of 166 articles, ultimately 41 articles were included in this study representing 877 patients (Figure 1, Table S1). 10–50 Ten studies were level of evidence 1, 30 studies were level of evidence 2, and 1 study was level of evidence four. Study types included placebo‐controlled trials ( n = 2), non‐placebo‐controlled trials ( n = 8), cohort studies ( n = 30) and case series ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…After Lee et al used FTL to treat Asian melasma in 2013 ( 20 ), more and more studies on treating post-inflammatory pigmentation by FTL have also been reported. After Bae et al ( 23 ) first uses FTL to treat PIH treatment, Alharbi found it was more friendly for patients with darker skin types ( 24 ). In addition, due to its possibly increased safety profile over other fractional lasers, FTL appears to have a significant role to play in the treatment of skin of color.…”
Section: Discussionmentioning
confidence: 99%